Marcação imuno-histoquímica de vegf e cox-2 no processo de reparo de enxerto ósseo particulado em defeito de calota craniana de coelhos e inibição de cox-2 - Comparin, Éliston (2012)
The major benefits achieved with maxillofacial rehabilitation, especially with regard to rehabilitation with dental implants osteointegráveis, encourage the development of techniques and materials, as well as the improvement in the understanding of the mechanisms of tissue repair, rehabilitation directly involved in the process. The presente study aimed to analyze the effect of inhibition of cyclooxygenase 2 (COX-2) during repair of bone graft particulate calvarial defect of rabbits. Twenty-four New Zealand male rabbits type were divided into two groups: Control group: treated with 0.9% saline, Group nonsteroidal anti-inflammatory drug (NSAID): etoricoxib treated daily with a dose of 6mg/kg orally. After periods of 7, 14 and 30 days the animals were euthanized and the grafted areas removed for microscopic morphological analysis, histomorphometry and immunohistochemistry for COX-2 and vascular endothelial growth factor (VEGF). Data from histomorphometric analysis were subjected to the Mann-Whitney test (percent), where there was a statistically significant difference between the control group (median 197 points) and the NSAID group (median 59 points) for the period and 14 days (median 237 points) and (median 68.5 points) respectively for 30 days. In immunohistochemical analysis using the COX-2 protein as a marker, we found that in 14 days, there was a more obvious bone formation in the control group, indicating that the absence of NSAIDs, improved bone healing in this period. We conclude that the use of NSAIDs delayed boné repair process for the Group NSAID within 14 and 30 days.